2019
DOI: 10.1002/star.201800231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resistant Maltodextrins and Resistant Starch on Human Gut Microbiota and Organic Acids Production

Abstract: This study is conducted to elucidate the effect of differently engineered resistant maltodextrin (RMD) and resistant starch (RS) on human intestinal microbiotal fermentation. Different types of RMD and RS are used as the sole carbon sources for bacteria in feces from healthy volunteers. The cultured samples are analyzed for changes in microbial groups from which the prebiotic index (PI) is calculated. The metabolic activity of the microbiotal communities is monitored by efficiency of carbon utilization and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The presence of these genes led to the hypothesis of the ability of these strains to allow the entry of starch degradation products, such as maltose, into the glycolytic pathway ( 19 , 35 ). Since not all the starch introduced in the diet is hydrolyzed by human enzymes, being partially available as an energy source for the gut microbiota ( 36 ), glucosidases might be of utmost importance for probiotics, allowing them to be competitive in the human gastrointestinal ( 37 ) and genitourinary ( 38 ) tracts. In addition, the starch fermentation by gut microbiota, including probiotics, produces as beneficial products the short-chain fatty acids (SCFAs) which are documented to have a relevant role in healthy aging and exploit anti-inflammatory and antiproliferative effects ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these genes led to the hypothesis of the ability of these strains to allow the entry of starch degradation products, such as maltose, into the glycolytic pathway ( 19 , 35 ). Since not all the starch introduced in the diet is hydrolyzed by human enzymes, being partially available as an energy source for the gut microbiota ( 36 ), glucosidases might be of utmost importance for probiotics, allowing them to be competitive in the human gastrointestinal ( 37 ) and genitourinary ( 38 ) tracts. In addition, the starch fermentation by gut microbiota, including probiotics, produces as beneficial products the short-chain fatty acids (SCFAs) which are documented to have a relevant role in healthy aging and exploit anti-inflammatory and antiproliferative effects ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This GI discomfort may occur as a result of TRM fermentation in the colon by gut microbiota. A previous study demonstrated that TRM was fermentable and, therefore, increased SCFA production as well as increased the number of faecal lactobacilli and bifidobacterial populations (50) . However, fermentation of RMD in the colon not only produces SCFA but also gases, such as CH 4 , H 2 and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…RS was fermented to a high amount of butyric acid and propionic acid. The chemically modified starch also showed a high probiotics index [ 76 ]. In other research, green banana starch, after treatment with the heat moisture in the presence of citric acid, was used to feed rats.…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 99%
“…In vitro digestibility tests of tapioca and maca starch esterified with citric acid indicated a slow digestion rate in term of the increase RS content [ 47 , 80 ]. Zdybel et al and Sorndech et al also reported a high resistance of potato or rice starch citrate to amylolysis [ 76 , 81 ]. Probably, the inhibited contact of digestive enzymes within the glucoside bonds of chemically modified starch appears due to the increased spatial hindrance resulting from the attachment of citric anhydride onto the starch molecule [ 63 ].…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 99%